Corpus Luteum Development and Function after Supplementation of Long‐Acting Progesterone During the Early Luteal Phase in Beef Cattle. Issue 1 (4th September 2013) - Pugliesi, G; Oliveria, ML; Scolari, SC; Lopes, E; Pinaffi, FV; Miagawa, BT; Paiva, YN; Maio, JRG; Nogueira, GP; Binelli, M
Contents Strategic supplementation of P4 may be used to increase conception rates in cattle, but timing of supplementation in relation to ovulation, mass of supplementary P4 and formulation of the P4‐containing supplement has not been determined for beef cattle. Effects of supplementation of long‐acting progesterone (P4) on Days 2 or 3 post‐ovulation on development, function and regression of corpus luteum (CL) were studied in beef cattle. Cows were synchronized with an oestradiol/P4‐based protocol and treated with 150 or 300 mg of long‐acting P4 on Day 2 or 3 post‐ovulation (6–7 cows/group). Colour‐doppler ultrasound scanning and blood sample collection were performed from Day 2–21.5. Plasma P4 concentrations were greater (p < 0.05) from Day 2.5–5.5 in the Day 2‐treated groups and from Day 3.5–5.5 in the Day 3‐treated cows than in the control group. CL area and blood flow during Day 2–8.5 did not differ (p > 0.05) among groups, suggesting no effect of P4 treatment on luteal development. The frequency of cows that began luteolysis before Day 15 was greater (p < 0.04) in cows treated with 300 mg than in the controls, but there were no differences between non‐treated and 150 mg‐treated cows. The interval from pre‐treatment ovulation to functional and structural luteolysis was shorter (p < 0.01) in the combined P4‐treated groups than in the control cows. In conclusion, was showed for the first time that long‐acting P4 supplementation on Day 2 or 3 post‐ovulation increases P4 concentrations for ≥3 day, has no effect on luteal development, but anticipates the beginning of luteolysis in beef cattle.